The Effectiveness of Rose and Jasmine Aromatherapy on Reducing Anxiety Levels in Postpartum Mothers - Lia; Venny Diah Ningsih; Zakiatun Navisah; Zahrotun Naqiyah Sabrina Putri (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
During the postpartum period, there are physical and psychological changes in the form of worry and fear in achieving a new role as a mother. This event naturally occurs after childbirth. There are several psychological disorders that occur in postpartum mothers in achieving their new role as mothers, including anxiety. Prevention that can be done to overcome anxiety in postpartum mothers, among others, is complementary therapy using aromatherapy. The purpose of this study was to determine the effectiveness of rose and jasmine aromatherapy to reduce anxiety levels in postpartum mothers. This type of research is quasi-experimental with a two group pretest and posttest design. The number of samples was 20 postpartum mothers with the total sampling method. Bivariate analysis with T Test Dependent test. The results showed that there was a significant effect before and after giving rose aromatherapy (p<0.05) and there was an effect before and after giving jasmine aromatherapy (p<0.05). There was no significant difference between giving rose and jasmine aromatherapy (p < 0.05) to decrease anxiety levels in postpartum mothers, so postpartum mothers can use rose and jasmine aromatherapy to reduce anxiety levels.